EFEKTIVITAS PEMUNGUTAN PAJAK BUMI DAN BANGUNAN UNTUK MENINGKATKAN PENDAPATAN ASLI DAERAH DI KECAMATAN AESESA KABUPATEN NAGEKEO - Dhiomang, Maria Evelin Sunga; Sayang, Sabulon; Kapa, Sesilianus (Program Studi Akuntansi Universitas Flores, 2020)
This study aims to determine whether the collection of Land and Building Tax (PBB) has been effective in increasing Regional Original Income (PAD) in Aesesa District, Nagekeo Regency. This research is a caulitative approach research with data collection techniques by means of observation, interviews and documentation studies as well as the research object of the Regional Finance Agency Office of Nagekeo Regency. The results of the research on the effectiveness of land and building tax (PBB) collection in Aesesa District, Nagekeo Regency, it is still found that the effectiveness of land and building tax revenues from 2014 to 2016 is categorized as ineffective with an average percentage for each year, from 2014 the percentage of the effectiveness ratio is 2%. In 2015 the percentage of the effectiveness ratio was 6% and in 2016 the effectiveness ratio was 54%. With regard to land and building tax revenues, this is in the ineffective category.